A Perfect Ground: preparatory layers for oil paintings 1550 - 1900 Maartje Stols-Witlox - Bruquetas Galán, Rocío (Ge-conservacion, 2018)
Perfect Ground: preparatory layers for oil paintings 1550 - 1900 Maartje Stols-Witlox ISBN: 9781909492356 Dimensiones: 246 x 175mm Páginas: 412 Ilustraciones en color